2005
DOI: 10.1583/05-1530r.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Adjusted Outcome Analysis of Endovascular Abdominal Aortic Aneurysm Repair in a Large Population:How Do Stent-Grafts Compare?

Abstract: ࡗ ࡗPurpose: To compare differences in the applicability and incidence of postoperative adverse events among stent-grafts used for repair of infrarenal aortic aneurysms.Methods: An analysis of 6787 patients from the EUROSTAR Registry database was conducted to compare aneurysm morphological features, patient characteristics, and postoperative events for the AneuRx, EVT/Ancure, Excluder, Stentor, Talent, and Zenith devices versus the Vanguard device (control) and each other. Annual incidence rates of complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 34 publications
(63 reference statements)
1
78
0
1
Order By: Relevance
“…Good results were noted in this era by several different units, and the A-U-I configuration appeared more durable. 14 In this study, open conversion did have a low mortality despite the majority of patients being originally regarded as unfit for open surgery. Similar findings were reported by other early studies.…”
Section: Discussionmentioning
confidence: 64%
“…Good results were noted in this era by several different units, and the A-U-I configuration appeared more durable. 14 In this study, open conversion did have a low mortality despite the majority of patients being originally regarded as unfit for open surgery. Similar findings were reported by other early studies.…”
Section: Discussionmentioning
confidence: 64%
“…Although several studies have reported results of EVAR with individual endografts 1-10 and a few have compared different stent grafts, [11][12][13][14][15][16][17][18][19] no comparison between the Talent bifurcated endograft and the Endofit AUI has been published until now. Many surgeons are reluctant to treat AAA with AUI extra-anatomical devices.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier EUROSTAR studies have chosen this threshold considering growth. [18][19][20][21] To account for relative AAA infrarenal neck changes during follow-up, an increase of Ն15% in transverse aortic neck diameter measured 3 mm distally from the lowermost renal artery was considered significant.…”
Section: Study Population and Organization Of The Eurostar Registrymentioning
confidence: 99%